E-048 Factors Associated with Early Tracheostomy and Percutaneous Gastrostomy and Their Effects on Hospitalization in Hemorrhagic Stroke Patients. (29th July 2016) - McCann, M; Fraser, J
Abstract : Objective: Tracheotomy and percutaneous endoscopic gastrostomy (PEG) are sometimes performed in critically ill hemorrhagic stroke patients in order to avoid complications associated with prolonged intubation and nasogastric feeding. However, there is a paucity of information regarding the optimal timing of these procedures. In this study, we aimed to evaluate the role of early tracheotomy and PEG in hemorrhagic stroke patients. Methods: A series of patients treated at University of Kentucky for hemorrhagic stroke between June 1, 2011 and June 1, 2015 was retrospectively reviewed. Data regarding diagnosis, demographics, comorbidities, treatment, hospital course, and performance of tracheotomy and/or PEG were collected and then analyzed using logistic regression and multiple linear regression. Results: Of 366 hemorrhagic stroke patients, 75 underwent tracheotomy and 86 received PEG. Factors significantly associated with tracheotomy and PEG included patient age (p < 0.01), pneumonia present on admission (p < 0.005), and subtype of hemorrhagic stroke (p < 0.05). Tracheotomy and PEG were not significantly associated with patient survival or development of complications. Earlier PEG placement was correlated significantly with shorter overall hospital stay in survivors (p < 0.001), but neither tracheotomy nor PEG was correlated with ICU length of stay. Conclusions: Hemorrhagic stroke is a devastating neurovascular event that requires prompt intervention and vigilant management. Our study identified patient risk factors that may suggest candidacy for tracheotomy and PEG. Additionally, we found that timing of PEG may shape a patient's hospital course. Complication rates related to tracheostomy and PEG in this population were minimal. In conclusion, this retrospective data set supports some benefit to early PEG placement in this population, and justifies the need for further prospective study. Disclosures: M. McCann: None. J. Fraser: None.